2011
DOI: 10.4061/2011/568918
|View full text |Cite
|
Sign up to set email alerts
|

Dyssynchrony Assessment with Tissue Doppler Imaging and Regional Volumetric Analysis by 3D Echocardiography Do Not Predict Long-Term Response to Cardiac Resynchronization Therapy

Abstract: Background. Currently there are no reliable predictors of response to cardiac resynchronization therapy (CRT) before implantation. We compared pre-CRT left ventricular (LV) dyssynchrony by tissue Doppler imaging (TDI) and regional volumetric analysis by 3-dimensional transthoracic echocardiography (3DTTE) in predicting response to CRT. Methods. Thirty-eight patients (79% nonischemic cardiomyopathy) with symptomatic heart failure who underwent CRT were enrolled. Clinical and echocardiographic responses were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A recently published study by Kuppahally et al 39 showed that dyssynchrony assessment using DTI and regional volumetric analysis by 3D echocardiography did not predict long‐term response to CRT. The possible explanation for the difference observed in the results between this study and our study may be the following.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study by Kuppahally et al 39 showed that dyssynchrony assessment using DTI and regional volumetric analysis by 3D echocardiography did not predict long‐term response to CRT. The possible explanation for the difference observed in the results between this study and our study may be the following.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite all efforts, prospective randomized, multicenter trials-such as the PROSPECT trial-failed to provide any reliable single echocardiographic parameter for dyssynchrony measurement that might improve patient selection for CRT beyond current guidelines. [17,18] Furthermore, the ECHO-CRT trial has shown that resynchronization therapy based solely on the presence of mechanical dyssynchrony (echocardiographic evidence of LV dyssynchrony) in NYHA III/IV HFrEF patients without electrical conduction disease (narrow QRS < 130 ms), did not improve outcome and was even associated with harm. [19] Cardiac magnetic resonance (CMR) has emerged during the last decade as the gold standard imaging technique for myocardial substrate assessment.…”
Section: Assessment Of Cardiac Dyssynchronyelectrical Versus Mechanicalmentioning
confidence: 99%